Menopausal symptoms are associated with oral sensory complaints in perimenopausal women: an observational study - Tomoharu Taga; Kayoko Ito; Kiyoshi Takamatsu; Mariko Ogawa; Saori Funayama; Makoto Inoue (BMC, 2021)
Abstract Background Perimenopausal women experience a wide variety of systemic symptoms: hot flashes, sweating, mental health concerns and various oral sensory complaints (OSC). OSC in perimenopausal women include xerostomia, taste disturbance and burning mouth. However, the factors associated with these OSC have not been identified. The purpose of this investigation was to elucidate the factors associated with OSC in perimenopausal women. Methods The study cohort comprised 43 perimenopausal women aged 45-55 years. Data on medical history, medications, menstrual status, menopausal symptoms, quality of life, xerostomia, taste disturbance and burning mouth were collected. Volumes of unstimulated and stimulated saliva were measured. Tongue coating was evaluated according to a tongue coating index. Univariate analysis was performed to identify factors significantly associated with having xerostomia, taste disturbance, burning mouth and more than two OSC (2OSC). Next, the factors strongly associated with these symptoms were examined by logistic regression analysis. Results The number of menopausal symptoms was significantly higher, and volume of unstimulated saliva was significantly lower in participants with xerostomia, taste disturbance, burning mouth or 2OSC than in those without these characteristics. Agents targeting the central nervous system were more frequently taken by participants with burning mouth and 2OSC than by those without these characteristics. According to logistic regression analysis, the number of menopausal symptoms was an explanatory variable for xerostomia, taste disturbance, burning mouth and 2OSC. Conclusions Our findings suggested that OSC associated with the number of menopausal symptoms. Management of menopausal symptoms may decrease OSC, leading to improved quality of life of perimenopausal women.